2016
DOI: 10.1007/s10995-016-2028-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stressful Life Events on Postpartum Depression: Findings from the 2009–2011 Mississippi Pregnancy Risk Assessment Monitoring System

Abstract: Objectives To determine the prevalence of postpartum depression (PPD) among new mothers in Mississippi during 2009–2011 and evaluate the effects of different stressful life events in the year before delivery on the likelihood of PPD. Methods We used Mississippi Pregnancy Risk Assessment Monitoring System (PRAMS) 2009–2011 data (n = 3695) to evaluate the effects of different stressful life events on PPD. We categorized 13 stressors into 4 groups: financial, relational, trauma-related, and emotional. A composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
34
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 27 publications
7
34
1
1
Order By: Relevance
“…Depresi pasca persalinan merupakan kondisi kesehatan mental yang mempengaruhi hingga 13% dari ibu primipara yang terjadi pada 4 minggu pertama hingga 1 tahun pasca persalinan (Qobadi, Collier and Zhang, 2016). Dukungan sosial yang rendah merupakan prediktor kuat dari depresi pasca persalinan (Negron et al, 2013).…”
unclassified
“…Depresi pasca persalinan merupakan kondisi kesehatan mental yang mempengaruhi hingga 13% dari ibu primipara yang terjadi pada 4 minggu pertama hingga 1 tahun pasca persalinan (Qobadi, Collier and Zhang, 2016). Dukungan sosial yang rendah merupakan prediktor kuat dari depresi pasca persalinan (Negron et al, 2013).…”
unclassified
“…The fifth edition of the diagnostic and statistical manual (DSM-V) described postpartum depression as a major depression along with the care of postpartum onset, a diagnosis that can be utilized signs manifest throughout being pregnant and within the four weeks after delivery (3). Some women may not experience PPD; however, mothers who are most at risk have a history of depression (4), substance use problems (5), high stress in life (6), poor socioeconomic status (7), 10.29252/johe. 8.3.141 and lack of social support (8,9); also they might be single (10) or old mother (11).…”
Section: Introductionmentioning
confidence: 99%
“…Stress is normally induced by a stimulus of a stressor which may include traumatic life events, and undesirable home or work environments, which would lead to the activation of the hypothalamic pituitary adrenal (HPA) axis and cortisol production, and potentially increased risk of postpartum depression [ 5 ]. Indeed, earlier studies had demonstrated the ability of maternal cortisol to cross the placenta to the fetus [ 6 ], where it can exhibit a repertoire of detrimental effects including impaired brain development and low birthweight of the offspring [ 7 ], thereby providing evidence for the undesirable effects of stress during pregnancy on the offspring.…”
Section: Introductionmentioning
confidence: 99%